Antibodies to myelin oligodendrocyte glycoprotein in optic perineuritis - Cao, Shanshan; Zhang, Yuan; Xu, Xintong; Sun, Mingming; Pan, Chunyan; Wang, Yuhang; Wei, Shihui; Xu, Quangang; Zhou, Huanfen (Frontiers in Immunology, 2025)
IntroductionThis study aimed to investigate the prevalence of myelin oligodendrocyte glycoprotein antibodies (MOG-IgG) in patients with optic perineuritis (OPN) and to analyze the clinical characteristics and prognosis of MOG-IgG–seropositive cases.MethodsA retrospective review was conducted of OPN patients diagnosed at the Neuro-ophthalmology Department of the Chinese People’s Liberation Army (PLA) General Hospital between January 2020 and February 2023. Patients were classified into MOG-IgG–positive and seronegative groups based on cell-based assay (CBA) results. Demographic data, clinical manifestations, and visual outcomes were compared between the two groups.ResultsA total of 33 patients (44 eyes) were included, with a mean onset age of 32.7 years (range 6–79) and a male-to-female ratio of 1:2. Bilateral involvement was observed in 33.3% of cases. Eye pain and optic disc swelling were present in 72.7% and 75.8% of patients, respectively. MOG-IgG was detected in 8 patients (24.2%). Compared with seronegative OPN, MOG-IgG-positive patients were significantly younger (mean age 20.8 years vs. 36.6 years, P = 0.034) and had a higher annual relapse rate (median 1.19 vs. 0.31, P = 0.008). All MOG-IgG-positive patients achieved visual acuity (VA) ≥20/40 after the first episode (100.0% vs. 45.5% in seronegative cases, P = 0.005), with this difference persisting at final follow-up (78.6% vs. 47.4%, P = 0.044).DiscussionThese findings highlight distinct clinical characteristics of MOG-IgG-positive OPN, including younger age, higher relapse rates, and superior visual recovery. Detection of MOG-IgG in OPN may facilitate early diagnosis, prognosis prediction, and guide individualized therapeutic strategies.